2013
DOI: 10.1007/s12035-013-8399-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Muscular Atrophy and the Antiapoptotic Role of Survival of Motor Neuron (SMN) Protein

Abstract: Spinal muscular atrophy (SMA) is a devastating and often fatal neurodegenerative disease that affects spinal motor neurons and leads to progressive muscle wasting and paralysis. The survival of motor neuron (SMN) gene is mutated or deleted in most forms of SMA, which results in a critical reduction in SMN protein. Motor neurons appear particularly vulnerable to reduced SMN protein levels. Therefore, understanding the functional role of SMN in protecting motor neurons from degeneration is an essential prerequis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 156 publications
0
13
0
Order By: Relevance
“…In regard to apoptosis and neurodegenerative disorders, a deregulation of this process is associated with a long list of pathologies (Marino et al, 2014). In SMA disease, genetic studies in mice (Kerr et al, 2000; Anderton et al, 2013) support a role for programmed neuronal death. Thus, in the central nervous system of SMA mouse models, elevated levels of pro-apoptotic genes and an enhancement of apoptosis have been observed (Tsai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to apoptosis and neurodegenerative disorders, a deregulation of this process is associated with a long list of pathologies (Marino et al, 2014). In SMA disease, genetic studies in mice (Kerr et al, 2000; Anderton et al, 2013) support a role for programmed neuronal death. Thus, in the central nervous system of SMA mouse models, elevated levels of pro-apoptotic genes and an enhancement of apoptosis have been observed (Tsai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SMN could play splicing-independent neuronal functions (FALLINI et al 2012;PRAVEEN et al 2012;LI et al 2014), such as axonal RNA transport (MCWHORTER et al 2003), organization of the neuromuscular junction (KARIYA et al 2014 ), and the control of proper muscle architecture (WALKER et al 2008). SMN also prevents accumulation of RNA-DNA hybrids, which is thought to result in DNA damage and apoptosis (ANDERTON et al 2013;ZHAO et al 2016), and is required for maintenance of embryonic stem cells and neuronal differentiation (EBERT et al 2009;CHANG et al 2015). However, direct evidence linking defects in these processes to SMA is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies detailing SMN's anti-apoptotic role will not be discussed here as this has been reviewed recently: SMN is involved in the modulation of apoptosis not only by blocking the activation of several caspases, but also by modulating other key regulators of cell survival [see Anderton et al, 2013]. The role of SMN in translational regulation has been uncovered recently by the demonstration that SMN is associated with polysomes; this association results in the repression of translation in vitro [Sanchez et al, 2013].…”
Section: Smn: How Many Functions Can a Single Protein Possess?mentioning
confidence: 99%